THE SELECTIVITY OF CYCLIZATION REACTION OF CITRONELLA BY FeCl3 AND ZnCl2 CATALYSTS - , Edy Cahyono and Sri Kadarwati ([Yogyakarta] : Fak. MIPA Universitas Gadjah Mada, 2007)
The cyclization of citronellal is an important step in menthol synthesis. The selectivity of FeCl3 and ZnCl2 catalysts was evaluated for this reaction. The cyclization reaction of citronellal was studied experimentally and theoretically. Citronellal was isolated using fractional distillation under reducing pressure. The reaction mixture contained citronellal, acetic anhydride, and Lewis acid with mol ratio of 2:6:1. The reaction was conducted at 80oC for 3 hours with stirring. FeCl3 and ZnCl2 catalysts showed high activity but low selectivity. The products were analyzed by means GC-MS and IR spectroscopy. The major products by FeCl3 catalyst were identified as p-cymene (36.13%) and citronellyl acetate isomeric (39.97%). At lower temperature, the replacement of FeCl3 by ZnCl2 showed the increasing of citronellyl acetate and isopulegyl acetate. The structures of reactants, products, and intermediates were studied by DFT/B3LYP method.